Comparative estimation of ErbB family growth receptors, Ki-67 and E-cadherin expression in pancreatic ductal adenocarcinoma cells - V. A. Tumanskiy; A. V. Evseyev (Zaporozhye State Medical University, 2014)
Aim. In immunohistochemical research of biopsy and postoperative material of 120 patients with the pancreatic ductal adenocarcinoma the levels of growth receptors of ErbB family and cancer prognostic markers expression were determined. Methods and results. Positive expression of EGFR by the tumour cells is determined in 87,5% of patients with ductal adenocarcinoma, simultaneously 77,5% of such patients had negative, and 13,33% of patients - doubtful HER-status. Expression of Ki-67 inductal carcinoma cells was found in 74,17% of patients, there were distinctions in expression of this marker within one tumour. The decline of expression of Е-cadherin was marked in 28,33% of patients with ductal adenocarcinoma, it was significantly more expressed in the areas of tumour invasion into the wall of duodenum. Conclusion. In patients with ductal adenocarcinoma direct correlation of medium strength between the levels of EGFR and HER-2/neu, EGFR and Кі-67, Кі-67 and HER-2/neu expression by the tumour cells is marked, inverse strong correlation between the level of EGFR and Е-cadherin expression, inverse correlation of medium strength between the level of expression of HER-2/neu and Е-cadherin, and between the level of Кі-67 and Е-cadherin expression there is weak inverse correlation.